2018
DOI: 10.1016/j.matlet.2017.11.067
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary investigation on the tribocorrosion behaviour of nanotubular structured Ti6Al4V surfaces

Abstract: a b s t r a c tIn order to improve its tribocorrosion resistance, nanotubular structures were produced on Ti6Al4V surfaces by anodic treatment in a mixture of 1 M H 2 SO 4 and 0.08 M HF electrolyte. Tribocorrosion tests were performed in a phosphate-buffered saline solution (PBS) against an alumina ball under 50 mN. Results showed that nanostructured surfaces exhibited significantly lower tendency to corrosion due to the protecting effect given by the well-adherent TiO 2 nanotubular layer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Recently, some of the present authors reported that the cast Ti-40Nb alloy had significantly lower tribocorrosion resistance compared to commercial Ti-6Al-4 V in a physiological solution at body temperature, pointing to the necessity of an appropriate modification for long term implantation [28]. The tribocorrosion resistance may be improved by the formation of an oxide nanotubular structure [32,34], however, it has been reported that the nanotubes grown on Ti had significantly poor adhesion to the substrate [43][44][45]. In this study, an additional oxide layer was formed at the interface between the bare metal and the nanotubes in order to overcome the poor adhesion of the TNT layer to the bare metal.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Recently, some of the present authors reported that the cast Ti-40Nb alloy had significantly lower tribocorrosion resistance compared to commercial Ti-6Al-4 V in a physiological solution at body temperature, pointing to the necessity of an appropriate modification for long term implantation [28]. The tribocorrosion resistance may be improved by the formation of an oxide nanotubular structure [32,34], however, it has been reported that the nanotubes grown on Ti had significantly poor adhesion to the substrate [43][44][45]. In this study, an additional oxide layer was formed at the interface between the bare metal and the nanotubes in order to overcome the poor adhesion of the TNT layer to the bare metal.…”
Section: Introductionmentioning
confidence: 68%
“…To improve the wear resistance of Ti and its alloys, TNT surfaces have been proposed and investigated in the literature. Rodrigues et al [32] showed that the tribocorrosion behavior of TNT grown on Ti-6Al-4 V alloy by anodic treatment in H 2 SO 4 based electrolyte during 1 h presented promising resulted in a significantly lower tendency to corrosion under sliding compared to the untreated alloy. However, after tribocorrosion tests, Alves et al [33,34] reported an easy detachment of the TNT layer, formed by anodic treatment in ethylene glycol-based electrolyte, while the tribocorrosion behavior of TNT layer grown on Ti was significantly improved by the formation of a thick oxide layer at the interface formed during an additional cycle of reverse polarization anodic treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Commercial cast and forged Ti6Al4V alloy usually presents a finely distributed α phase and a relatively smaller percentage of β phase distributed along the grain boundaries of the α phase, as also presented by Karimzadeh et al (2008) and Rodrigues et al (2018). These phases were also reported for the HP alloy by Buciumeanu et al (2017) and Gronostajski et al (2009), however, with a different morphology, namely a lamellar structure.…”
Section: Microstructuresmentioning
confidence: 95%
“…From 2018 to 2021, the effects of electrolyte composition in the Micro-Arc Oxidation (MAO) process on cp-Ti and Ti-6Al-4V were studied. These studies highlighted how the addition of bio-active elements (Ca and P) optimized the tribocorrosion behavior, surface hardness and microstructure [168][169][170][171]. For the Ti40Nb alloy, a two-step anodic treatment and heat treatment were employed to develop a TiO 2 -based nanotubular surface with improved adhesion, further enhanced by the addition of an extra oxide layer from a fluoride-free electrolyte [172].…”
Section: Dentalmentioning
confidence: 99%